Soil extracellular polymeric substances and microbial biomass react differently to field induced drought stress in contrasting cropping systems at different wheat developmental stages - Bublitz, Tabata Aline; Kost, Elena; Kundel, Dominika; Alimi, Oluwaseun ldowu; Hupe, Anke; Mäder, Paul; Krause, Hans-Martin; Mayer, Jochen; Hartmann, Martin; Joergensen, Rainer Georg (Biology and fertility of soils, 2025)
Drought events are becoming more severe and recurrent over Europe. Changes in temperature and rain patterns can affect soil nutrient mobility and availability, modulating the biomass and activity of soil microbial communities. Here, we investigated the effects of drought on extracellular polymeric substances (EPS) and microbial biomass carbon (MBC) and nitrogen (MBN) in differently managed cropping systems. An on-field drought simulation experiment using rain-out shelters was conducted as part of a long-term field experiment cultivated with winter wheat, comparing cropping systems with contrasting fertilization strategies and crop protection measures: A biodynamic system and a mixed conventional system with no pesticide application, and a purely minerally fertilized conventional system, with conventional pesticide use. The implemented drought lasted for three months, starting at plant tillering stage and ending at ripening stage. No watering was performed on the drought treatment during that period. Soils were sampled at stem elongation, flowering, and ripening. EPS-carbohydrates and EPS-proteins significantly increased by approximately 20% due to induced drought but remained roughly constant from stem elongation to ripening under drought. Mean EPS-carbohydrates to EPS-proteins ratio was 1.9. MBC and MBN remained largely unaffected by drought. The ratio of both EPS fractions to microbial biomass was lowest in the biodynamic system and highest in the minerally fertilized conventional system, indicating that rhizodeposits and mucilage were predominantly diverted into microbial biomass, rather than into microbial EPS. This might be an important reason for the higher soil fertility of the biodynamic system.